2015
DOI: 10.1371/journal.pntd.0003430
|View full text |Cite
|
Sign up to set email alerts
|

Ribose 5-Phosphate Isomerase B Knockdown Compromises Trypanosoma brucei Bloodstream Form Infectivity

Abstract: Ribose 5-phosphate isomerase is an enzyme involved in the non-oxidative branch of the pentose phosphate pathway, and catalyzes the inter-conversion of D-ribose 5-phosphate and D-ribulose 5-phosphate. Trypanosomatids, including the agent of African sleeping sickness namely Trypanosoma brucei, have a type B ribose-5-phosphate isomerase. This enzyme is absent from humans, which have a structurally unrelated ribose 5-phosphate isomerase type A, and therefore has been proposed as an attractive drug target waiting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Recombinant enzymes from L. donovani 17, T. brucei 18 and T. cruzi 9 have been formally demonstrated to have in vitro isomerase activity, catalyzing the interconversion of R5P and Ru5P. In this paper we have demonstrated that the same applies to L. infantum and L. major homologues.…”
Section: Discussionmentioning
confidence: 63%
“…Recombinant enzymes from L. donovani 17, T. brucei 18 and T. cruzi 9 have been formally demonstrated to have in vitro isomerase activity, catalyzing the interconversion of R5P and Ru5P. In this paper we have demonstrated that the same applies to L. infantum and L. major homologues.…”
Section: Discussionmentioning
confidence: 63%
“…Biological benefits of multiple alleles at ribose 5‐phosphate isomerase is less obvious; however, the gene has been investigated as a drug target in treating Trypanosoma brucei , the cause of African sleeping sickness (Loureiro et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Glycogen storage may be important for L3 as during host invasion the L3 worm becomes highly motile as it must migrate from the site of inoculation to the human lymphatics. Biological benefits of multiple alleles at ribose 5-phosphate isomerase is less obvious; however, the gene has been investigated as a drug target in treating Trypanosoma brucei, the cause of African sleeping sickness (Loureiro et al 2015).…”
Section: Regions Of the Genome Possibly Influenced By Natural Selectionmentioning
confidence: 99%
“…An adverse phenotype was observed in E. coli [258] and also humans [259] upon RPI deficiency, suggesting a critical conserved role through evolution. Trypanosomatids possess a type B RPI, which is absent from humans that instead have a structurally unrelated type A and therefore possibly an ideal drug target [260][261][262][263][264][265]. Recombinant enzymes from L. donovani [262], L. infantum [261], L. major [261], T. brucei [263] and T. cruzi [263,264] have been formally demonstrated to have in vitro isomerase activity by catalysing the interconversion of R5P and Ru5P.…”
Section: Non-oxidative Branchmentioning
confidence: 99%
“…Trypanosomatids possess a type B RPI, which is absent from humans that instead have a structurally unrelated type A and therefore possibly an ideal drug target [260][261][262][263][264][265]. Recombinant enzymes from L. donovani [262], L. infantum [261], L. major [261], T. brucei [263] and T. cruzi [263,264] have been formally demonstrated to have in vitro isomerase activity by catalysing the interconversion of R5P and Ru5P. The Km values for both R5P and Ru5P were similar between Leishmania and trypanosomes enzymes, however, Kcat values are considerably higher for Leishmania, in both direct and inverse reactions [261][262][263][264].…”
Section: Non-oxidative Branchmentioning
confidence: 99%